Subjective well-being examined from sincerity and gratitude among cleaning service personnel - Hasanah, Nisaul; Novembli, Meta Silfia; Iskandar, Puteri Qohimah Hanum; Sindiasari, Dita (Empathy : Jurnal Fakultas Psikologi, 2023)
Cleaning service roles hold a low position within an employment institution. Low wages evoke negative feelings, job dissatisfaction, and disappointment, which are characteristics of individuals with low  subjective well-being. Sincerity and gratitude are among the factors that can influence subjective well-being. This study aims to determine if there is a relationship between sincerity and gratitude concerning the subjective well-being of cleaning service personnel. This research is quantitative, utilizing scales for sincerity, gratitude, and subjective well-being. The population comprises cleaning service personnel at the Indonesian Islamic University, with a sample size of 52 individuals chosen through random sampling. The findings indicate that there is no association between sincerity and gratitude concerning subjective well-being among cleaning service personnel. Additionally, no correlation was found between sincerity and subjective well-being, nor between gratitude and subjective well-being. The study concludes that the level of sincerity and gratitude does not impact the level of subjective well-being among cleaning service personnel.